Studi terhadap surat kuasa membebankan hak tanggungan (skmht) dalam perjanjian kredit pemilikan rumah (kpr) Bank Tabungan Negara (BTN) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Abstract Act 4 of 1996 aims to give foundation on how to enforce strong surety rights, for example on the enforcement of letter of giving surety rights. In circumstances that person who gives letter of giving surety rights is not able to come to the notary, article 15 (1) of the Act gives an opportunity to whom who give it using this right. The making of giving surety rights is also possible on land which does not have land certificate. This is what happens in the agreement on selling and buying house. Key words: surety rights, notary